The Shareholder Value Effect of System Overloads: An Analysis of Investor Responses to the 2003 Blackout in the US - Bouzzine, Yassin Denis; Lueg, Rainer (International Journal of Energy Economics and Policy, 2021)
This study investigates the stock price reaction of electric energy utility firms to the 2003 blackout in the Northeast of the USA and if the market was able to identify the responsible firm. Therefore, we employ event study methodology and select a sample of US-based electric energy utility firms. Although it took a commission almost eight months to name the firm responsible for the blackout, investors punished FirstEnergy only two trading days after the blackout - and were right, as it later turned out. This study demonstrates this based on the analysis of abnormal stock returns and abnormal trading volumes. Our findings suggest that investors have extensive knowledge of electric energy utility firms’ responsibility as they were able to identify the culprit. This, in turn, demonstrates that electric power utility firms should ensure a high-quality grid infrastructure to avoid these negative outcomes. Keywords: Event study; Blackout; System overload; Market efficiency JEL Classifications: G1, Q40 DOI: https://doi.org/10.32479/ijeep.11756